FRONT END CIRCUIT AND ENCODER - HIRATA SHU; TAWARA TOSHIHIRO; MUGIKURA SHUN; KAWAI AKIO (2022)
To provide a front end circuit capable of reducing influence by the offset voltage of an amplifier.SOLUTION: A front end circuit includes: a pre-stage amplifier 1 for amplifying input signals IN+ and IN-; a switching circuit 4 for alternatively inputting the input signals IN+ and IN- into the input terminals 1A and 1B of the pre-stage amplifier 1; a switched capacitor circuit 2 for sampling the input signals IN+ and IN- amplified by the pre-stage amplifier 1; an integration circuit 3 for outputting a differential signal obtained by integrating two sampled signals; and a switching circuit 5 constituted to switch a connection relationship between the switched capacitor circuit 2 and the integration circuit 3. The switching circuits 4 and 5 switch connection relationships between the pre-stage amplifier 1 and the input terminals TIN+ and TIN- and a connection relationship between the switched capacitor circuit 2 and the integration circuit 3 so as to sample the input signals IN+ and IN- amplified by the pre-stage amplifier 1 with double correlation.SELECTED DRAWING: Figure 6 【課題】増幅器のオフセット電圧による影響を低減できるフロントエンド回路を提供すること。【解決手段】前段増幅器１は、入力信号ＩＮ＋及びＩＮ－を増幅する。切替回路４は、入力信号ＩＮ＋及びＩＮ－を前段増幅器１の入力端子１Ａ及び１Ｂへ択一的に入力する。スイッチトキャパシタ回路２は、前段増幅器１で増幅された入力信号ＩＮ＋及びＩＮ－をサンプリングする。積分回路３は、サンプリングされた２つの信号を積分した差動信号を出力する。切替回路５は、スイッチトキャパシタ回路２と積分回路３との間の接続関係を切り替え可能に構成される。切替回路４及び５は、前段増幅器１で増幅された入力信号ＩＮ＋及びＩＮ－が二重相関サンプリングされるように、前段増幅器１と入力端子ＴＩＮ＋及びＴＩＮ－との間の接続関係及びスイッチトキャパシタ回路２と積分回路３との間の接続関係を切り替える。【選択図】図６